(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This study investigates the most effective teaching methods for enhancing practical and diagnostic skills among engineering students. Recognizing the increasing demand for engineers to possess not only theoretical knowledge but also hands-on experience and problem-solving capabilities, this research focuses on various pedagogical approaches, including project-based learning (PBL), simulation-based training, collaborative learning, and experiential learning. Data was collected through surveys and interviews with students and faculty across several engineering programs, supplemented by an analysis of academic performance metrics. Results indicate that students exposed to a combination of these teaching methods demonstrate significantly improved practical and diagnostic skills. The findings support the integration of these methodologies into engineering curricula to better prepare students for real-world challenges.